The importance of natural habitats to Brazilian free-tailed bats in intensive agricultural landscapes in the Winter Garden region of Texas, United States. (October 2015) - Davidai, Noa; Westbrook, John K.; Lessard, Jean-Philippe; Hallam, Thomas G.; McCracken, Gary F.
Abstract: The conversion of natural lands to agriculture is a leading cause of the worldwide loss of biodiversity. In particular, cropland monocultures alter insect abundance and diversity compared to adjacent natural habitats. While agricultural lands can provide large numbers of insect pests as prey items to predators such as bats, insect pest population size vary greatly throughout growing seasons. This study assesses the importance of land use and corn earworm moth availability as spatial and temporal drivers of bat activity. We quantified spatial variation in land use patterns at fifteen sites located within the Winter Garden region in south central Texas and used bat detectors and insect pheromone traps to monitor nightly bat activity and corn earworm moth abundance across the landscape and throughout most of the year. Our temporal analyses show that bat activity was positively correlated with moth abundance, but only early in the growing season when moth abundance is at its peak. The key result from this study is a positive relationship between bat activity and natural habitat cover during late summer months, corresponding to periods of low moth abundance and a peak in bat activity. During the late summer period, bats were more active at sites containing a larger percentage of natural habitats than those containing a larger percentage of agricultural land. Our results strongly suggest that intensive agricultural practices create systems providing bats with inconsistent resource supply, but the persistence of natural habitats provides consistency in food supply though time. Taken together, these findings illustrate the importance of protecting and restoring natural habitats for the conservation for bats and the pest-suppression services they provide in agricultural ecosystems.